2009
DOI: 10.1590/s1806-37132009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Tireoide ectópica no mediastino anterior

Abstract: A ectopia de tireoide é rara, e a sua localização no mediastino anterior é excepcional, estando descritos apenas 5 casos nos últimos 30 anos. Os autores apresentam 2 casos clínicos, além de uma revisão da literatura abordando a etiologia, a embriologia e manifestações clínicas de ectopia de tireoide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
(20 reference statements)
0
29
0
Order By: Relevance
“…Less commonly, patients may present with dysphagia or the superior vena cava syndrome. Intrathoracic thyroid may also be revealed incidentally on chest radiograph (34)(35)(36) or on autopsy (37). In cases of mediastinal ectopic thyroid, orthotopic tissue usually coexists and the patients are euthyroid (36).…”
Section: Other Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Less commonly, patients may present with dysphagia or the superior vena cava syndrome. Intrathoracic thyroid may also be revealed incidentally on chest radiograph (34)(35)(36) or on autopsy (37). In cases of mediastinal ectopic thyroid, orthotopic tissue usually coexists and the patients are euthyroid (36).…”
Section: Other Sitesmentioning
confidence: 99%
“…Intrathoracic thyroid may also be revealed incidentally on chest radiograph (34)(35)(36) or on autopsy (37). In cases of mediastinal ectopic thyroid, orthotopic tissue usually coexists and the patients are euthyroid (36). In most of the few cases been reported in the literature, it is located in the anterior mediastinum and in two cases posteriorly (36).…”
Section: Other Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…A thoracoscopic approach was the first choice in this case but transverse neck incision assistance was performed due to the incomplete exposure of the anterior mass. Ectopic thyroid should be considered during the diagnosis of mediastinal masses as there is a risk of hypothyroidism after surgery if the ectopic thyroid is nonfunctional [14]. …”
Section: Discussionmentioning
confidence: 99%
“…It is observed through radiation screening and CT scans and is reported to cause dry cough, dyspnea, hemoptysis aphagia, and superior vena cava syndrome. In addition, it is reported that orthotropic thyroid coexists in all cases of intrapulmonary thyroid [4,5]. Radiologic examinations for diagnosis include CT, magnetic resonance imaging, Tc-99m, I-131, and I-123.…”
Section: Discussionmentioning
confidence: 99%